Urgensi Terhadap Pembentukan Rancangan Peraturan Daerah Kota Samarinda Tentang Penyiaran Televisi Kabel Berlangganan - INSAN TAJALI NUR (Jurnal Risalah Hukum, 2008)
Human desire to entertainment amusement world and information there are and started since aperiod of history. But that way, we cannot get out of negative impact which marked by article appearance,news, picture, advertisement and display signalizing pornography, porno action, mystique, kriminal andother which do not in line with religion , cultural and social norms of Indonesian nation which containedin Five Principles and Peraturan Perundang- Undangan State Philosophy Republic Of Indonesia. Since itcannot deny that television represent one of the electronic media medium which enthused by many worldsociety. Not yet it him clarity to legal fundament and arrangement taken as Guidance to observation andmanagement of Channel cable television subscribe to in town of Samarinda represent challenge togovernment of town of Samarinda to immediately to make an policy in the form of containing by law ofprohibited rights,which executed,an matter and also sanction to side which impinge good by law rule toentrepreneur of cable television subscribe to, institute and society in charge arrange and observe allactivity related to cable television channel.Key words : raperda televise kabel (draft by rule district area of cable television), eksekutif (executive),legislatif (legislative), masyarakat (society), pengusaha (entrepreneur).